Factors influencing the adoption of m-commerce: a literature review - Sadi, A.H.M. Saifullah; Noordin, Mohamad Fauzan (2009)
Mobile Commerce also known as M-commerce is thought to be the next big phase in technologically dependent society after following E-commerce era. Mobile commerce has been a huge success in terms of individuals’ adoption in some markets like Japan, while, surprisingly, not as flourishing in others. Many studies have been conducted using traditional adoption models and theories (such as TAM) that mainly focus on technology aspects. A more complete understanding of the issue requires the need to integrate. This study aims to identify some factors from the current literature that impact the adoption of M-commerce. Based on the literature this study develops Mcommerce adoption framework. The contribution of this research is a framework for representing the factors that influence mobile commerce adoption.